The other side of the island - Goodman, Allegra (Razorbill, 2008)
Honor, living with her mom and dad on Island 365 in the Tranquil Sea, an environment controlled by the Earth Mother corporation in a post-apocalyptic world, becomes more fearful as she grows older and realizes that her nonconformist parents are putting the entire family at risk.